Resource-Making and Proto-Institutions in the German Tafel Field: Applying a Hermeneutical Context Model - Michaela Haase; Ingrid Becker (Journal of Contextual Economics – Schmollers Jahrbuch, 2020)
This paper studies resource making and the emergence of proto-institutions in Tafel Deutschland, an umbrella organization for more than 940 food banks or pantries in Germany, deploying a hermeneutical context model. Shedding light on value co-creation processes in the German Tafel field, we analyze how the activities and interpretations of or within Tafel organizations devoted to resource integration and resource making relate to their two missions and how their methods of dealing with conflict have led to the emergence of proto-institutions. The economic value co-created within in the Tafel field builds on the creation of social and ecological value. The context affects economic and social value co-created within the Tafel field differently: Whereas economic value rests on individual experience and perception, the social value resulting from the field actors' activities is subject to dispute and defense.
Keywords: A13; B52; B55; M31; 330; Hermeneutical Context Model; German Food Banks; Proto-Institutions; Resourceness; Value Co-creation